Report on industrial attachment with United Test and Assembly Centre UTAC - Saw, Michael Jun Min. (2008)
The purpose of this report is to state the some of the most significant projects undertaken during my term of Industrial Attachment in UTAC, United Test and Assembly Centre. This report will discuss on the some of the issues faced, strategies used and solutions used, in this period of industrial attachment in UTAC.